2021
DOI: 10.1021/acscatal.1c01382
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Origin of Organic Electrosynthesis Controlled by Electrode Materials: A Case Study on Pinacols

Abstract: Unveiling the origin of an electrode's ability to control the reaction outcome and identifying key factors to explore a promising electrode for selective synthesis of value-added chemicals are highly desirable for minimizing the reliance on the dominant trial-and-error screening mode of electrode materials. Here, the electroreductive pinacol coupling of aromatic carbonyl compounds in an alkaline solution was selected as a model; a hydrogen adsorption free energy (ΔG H* ) far from 0, the specific aryl ring adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 78 publications
4
53
0
Order By: Relevance
“…One such example is the reductive dimerization of furfural or HMF to form pinacol-like products (Figure ). It is believed that this reaction involves the formation of a ketyl radical intermediate. ,, Both outer sphere and inner sphere reaction mechanisms have been proposed. , …”
Section: Electrochemical Reductive Valorization Via Hydrogenation And...supporting
confidence: 82%
See 1 more Smart Citation
“…One such example is the reductive dimerization of furfural or HMF to form pinacol-like products (Figure ). It is believed that this reaction involves the formation of a ketyl radical intermediate. ,, Both outer sphere and inner sphere reaction mechanisms have been proposed. , …”
Section: Electrochemical Reductive Valorization Via Hydrogenation And...supporting
confidence: 82%
“…Several recent studies have found that the initial H-atom addition to generate the ketyl radical on route to pinacol formation does not involve the formation and transfer of H ads , unlike hydrogenation of the aldehyde group to form an alcohol. ,, This agrees well with the observations that pinacol formation is favored in a low overpotential ,, region where H ads cannot form and with electrodes that are poor at forming H ads such as C, , Pb, ,, In, and Au . It has also been reported that pinacol formation is favored when a higher concentration of HMF or furfural is used because this has the effect of promoting the formation of the ketyl radical over H ads . ,, …”
Section: Electrochemical Reductive Valorization Via Hydrogenation And...mentioning
confidence: 99%
“…Electrochemical pinacol coupling would be a promising alternative to avoid the use of low-valent metal reductants. The reported methods commonly carried out in a divided cell [29][30][31][32][33][34] or an undivided cell with sacrificial anodes [35], such as Al, Mg, and Sn, to prevent undesired oxidative reactions (Scheme 1b) [36][37][38][39]. While sacrificial anodes enable the reactions to be performed with a simple and user-friendly undivided cell set-up, consuming the anode material with generating stoichiometric metal waste may be a serious issue in terms of green and sustainable chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, cross-coupling product 3a was isolated in 81% yield (Table , entry 1). As a result of GCMS analysis of the reaction solution, deoxyhydrogenation of 1b (4-methyl-1,1′-biphenyl) and self-coupling of 2a (1,2-diphenylethane-1,2-diol) were found as the side reactions. The Faradaic efficiency of this reaction was calculated to be 27% (3.7 F).…”
mentioning
confidence: 99%